2012
DOI: 10.1007/s10856-012-4706-3
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of biocompatible titanium scaffolds using space holder technique

Abstract: Open-pore titanium scaffolds were fabricated by sintering of compressed mixtures of TiH(1.924) and urea. Spherical and irregular shaped space holders were used to investigate the effect of pore shape on cellular behavior. After removal of the space holder, the shape of the spacers was replicated to the pores. Average diameter of the pores was in the range of 300-600 μm. SEM images showed that titanium hydride resulted in higher surface roughness and larger micro porosities than pure titanium. In vitro evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…A series of in vitro cell compatibility tests, such as those shown in Figure 3, showing bone cell attachment, proliferation and differentiation in the Ti-Nb-Zr alloy scaffold, confirmed the biocompatibility of the scaffold produced with the space holder method [45]. This finding was attributed to the ability of the space holder method to produce high-porosity scaffolds (up to 70%) with interconnected pores, considering the great importance of porosity for bone cell activities [32,46]. …”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…A series of in vitro cell compatibility tests, such as those shown in Figure 3, showing bone cell attachment, proliferation and differentiation in the Ti-Nb-Zr alloy scaffold, confirmed the biocompatibility of the scaffold produced with the space holder method [45]. This finding was attributed to the ability of the space holder method to produce high-porosity scaffolds (up to 70%) with interconnected pores, considering the great importance of porosity for bone cell activities [32,46]. …”
Section: Introductionmentioning
confidence: 78%
“…The space holder method may also be called the fugitive filler method [27], considering the similarities in the principle of these two fabrication methods. A number of space holder materials have been utilized, such as carbamide (CO(NH 2 ) 2 ) [2832], ammonium hydrogen carbonate (NH 4 HCO 3 ) [33,34], sodium chloride (NaCl) [35,36], starch [37,38], saccharose [39], polymethyl-methacrylate (PMMA) [40], magnesium (Mg) [41,42], steel [43] and paraformaldehyde [44]. …”
Section: Introductionmentioning
confidence: 99%
“…Highly porous scaffolds were also obtained by the space holder method. While Dezfuli et al [14] observed excellent attachment and proliferation of human cells to scaffolds fabricated with urea, in the studies by Reig et al [15,16], of all the parameters influencing the mechanical properties of the porous samples developed, the amount and size of spacer particles, together with the compacting pressure, proved to be the most essential.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, researchers have done much work to investigate the effects of macropore size on bone ingrowth into the scaffold. The results suggested that the macropore size ranging from 100 to 500 μm could be the optimal pore size for bony ingrowth [18,34,35]. Recently, some researchers reported that the micropores distributed on the wall of the macropores may have positive effects on new bone formation [36].…”
Section: Resultsmentioning
confidence: 99%